DETERMINAN CADANGAN DEVISA DI NEGARA ORGANISASI KERJASAMA ISLAM (OKI) - Weri Mahendra; Fathiyyatur Rahmah; Zahra Ramadani Jasman (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2022)
This study was conducted to determine whether exports, remittances, exchange rates and inflation can affect the increase in foreign exchange reserves of the Islamic Cooperation Organization (OIC) in 2011-2020. The results of the study show that exports and remittances have a positive and significant effect on foreign exchange reserves. Meanwhile, the exchange rate does not have a positive and significant effect on foreign exchange reserves and inflation does not have a significant negative effect on the OIC's foreign exchange reserves.